A broad scale seabed substrate map of the Portuguese coast - Martins, R. (2015)
The MeshAtlantic project aimed to generate a broad-scale habitat map for the shelf and coastal area of the Atlantic Area. Till 2012, a detailed seabed substrate map of the Portuguese coast, which covers a great extension of the Western Iberian coast, was not known.